Nanocomposites of Bi5FeTi3O15 with MoS2 as novel Pt-free counter electrode in dye-sensitized solar cells. Issue 11 (15th August 2016) - Liang, X.; Zheng, H.W.; Li, X.J.; Yu, Y.H.; Yue, G.T.; Zhang, W.; Tian, J.J.; Li, T.F.
Abstract: Bi5 FeTi3 O15 (BFTO) nanofibers with diameters in the range of 40–100 nm have been fabricated by sol-gel based electrospinning technique. The structure and morphology of the nanofibers were characterized by X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. The MoS2 nanoparticles are uniformly dispersed into the BFTO, forming nanocomposites. The optical bandgap of the nanocomposites decreases as MoS2 content increases. The nanocomposites with different MoS2 contents serve as low-cost counter electrodes (CEs) for dye-sensitized solar cells (DSSCs). Through photocurrent–voltage curves, electrochemical impedance spectroscopy and Tafel curves, the performance of the CEs indicates that the charge transfer resistance on the electrolyte-electrode interface lower and the catalytic activity for reduction of triiodide to iodide enhance with the increase of MoS2 concentration. The DSSC with the CE exhibits a power conversion efficiency of 5.20% after the optimization of the content of MoS2, which is almost 24 times larger than that of the pure BFTO CE.